Hasil Keputusan Nilai Preferensi Metode Simple Additive Weighting Terhadap Rekomendasi Wisata Sejarah di Kepulauan Seribu - Fata Nidaul Khasanah; Timorora Sandha Perdhana; David Nurmanto (Faculty of Computer Science, University of Jember, 2022)
One of the great potentials that can improve the economy of local communities is development in the tourism sector. Kepulauan Seribu is an archipelago area in the north of Jakarta, this area has tourism potential in the form of a cluster of islands. This group of islands has different characteristics to be used as a tourist attraction, including marine tourism, historical tourism and nature reserve tourism (conservation). Historical tourism in the Kepulauan Seribu has its own charm judging from the historical relics of the Netherlands before Indonesian independence. Islands that have historical tourism potential are the reason for conducting research related to the selection of tourist destinations in the Kepulauan Seribu, such as Kelor, Onrust and Cipir island. The obstacles of the community in finding the right tourism potential are still lacking information from the aspects of attractions, accessibility and facilities. To assist tourists in choosing a place, a decision support system is needed that can be completed using the Simple Additive Weighting method. There are five assessment criteria including scenery, photo spots, transportation, toilets and places to eat/resto. Determination of weights on criteria using a statistical approach from the questionnaire results shared with a likert scale. The result of the preferred tourist recommendation preference value is the island of Kelor because there are seven highest scores obtained by the island compared to Onrust island and Cipir island.